DDX1 is required for non-spliceosomal splicing of tRNAs but not of XBP1 mRNA - Teruhiko Suzuki; Satoko Takagi; Junta Funada; Yuka Egawa; Mana Yamakawa; Takahiko Hara (Communications Biology)
Abstract RNA helicase DEAD-box helicase 1 (DDX1) forms a complex with the RNA ligase 2´,3´-cyclic phosphate and 5´-OH ligase (RTCB), which plays a vital role in non-spliceosomal splicing of tRNA and X-box binding protein 1 (XBP1) mRNA. However, the importance of DDX1 in non-spliceosomal splicing has not been clarified. To analyze the functions of DDX1 in mammalian cells, we generated DDX1 cKO cells from the polyploid human U2OS cell line and found that splicing of intron-containing tRNAs was significantly disturbed in DDX1-deficient cells, whereas endoplasmic reticulum (ER) stress-induced splicing of XBP1 mRNA was unaffected. Additionally, the enforced expression of DDX1, but not of its helicase-inactive mutant, rescued the splicing defects of tRNAs in DDX1-deficient cells. These results indicate that RTCB is required for the splicing of both tRNA and XBP1 mRNA, whereas the DDX1 enzymatic activity is specifically required for tRNA splicing in vivo.